Antimetastatic and antiangiogenic activity of trabectedin in cutaneous melanoma. (24th December 2018) - Carminati, Laura; Pinessi, Denise; Borsotti, Patrizia; Minoli, Lucia; Giavazzi, Raffaella; D'Incalci, Maurizio; Belotti, Dorina; Taraboletti, Giulia
Abstract: Trabectedin is a marine-derived antineoplastic drug. Besides targeting the cancer cells, trabectedin has a peculiar activity on the tumor microenvironment with marked effects on the vasculature and the immune response. Because a favorable microenvironment is a key factor in the progression of cutaneous melanoma, we hypothesized that trabectedin might affect the growth and metastasis of this highly aggressive cancer. This study shows that trabectedin inhibited the subcutaneous growth of the murine melanoma B16-BL6 and K1735-M2. In line with its known activities on the environment of other tumor types, it caused a significant reduction of tumor blood vessel density and tumor-associated macrophages. Trabectedin had a significant antimetastatic activity, inhibiting the formation of lung colonies following intravenous injection of B16-BL6 or K1735-M2 cells. The drug was also active in a clinically relevant spontaneous metastasis assay, where it inhibited lung metastasis when administered before (neoadjuvant) or after (adjuvant) surgical removal of the primary tumor. Relevant to its antimetastatic activity, trabectedin inhibited melanoma cell invasiveness in vitro, associated with increased tissue inhibitor of metalloproteinase-1 production and alteration in cell shape and cytoskeleton organization. This study shows that trabectedin affects melanoma growth and metastasis, acting with tumor-dependent mechanisms on both the tumor cells and the vascular and the inflammatory tumor microenvironment. Abstract : Identifying new treatment strategies for melanoma is still a major clinical need. This study shows that trabectedin has antineoplastic and an excellent antimetastatic activity in preclinical melanoma models, targeting both the tumor cells and the tumor microenvironment.